TASAWWUF OF THE PROPHET - Mahdiah Mahdiah (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2020)
Sufism is one of the fields of Islamic studies that focuses on cleansing the spiritual aspects of humans which can then lead to noble character. The cleansing of this spiritual or inner aspect is hereinafter known as the esoteric dimension of the human self. Islam as a religion that is universal and includes various answers to various human needs, in addition to requiring outward cleanliness also requires inner cleanliness, because the real assessment in Islam is given to the inner aspect. This can be seen, for example, in one of the conditions for the acceptance of acts of worship, which must be accompanied by an intention. Through this study of Sufism, one can find out about ways to do self-cleaning and practice it properly. From this knowledge, it is hoped that he will appear as a person who is good at controlling himself when interacting with other people, or when carrying out various world activities that require honesty, sincerity, responsibility, trust and so on. From such an atmosphere, Sufism is expected to overcome various moral deviations that take the form of manipulation, corruption, collusion, abuse of power and opportunity, oppression. Therefore, Sufism can enter every line of human life or in other words it can affect all aspects of human life, as the development of Sufism has also existed since the previous prophets of God